1997
DOI: 10.1002/hlca.19970800407
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II)‐Catalyzed CH Insertions with {[(4‐Nitrophenyl)sulfonyl]imino}phenyl‐λ3‐iodane

Abstract: Dedicated to Prof. Dieter Seebach on the occasion of his 60th birthday (1 3.11.97) The [Rh,(OAc),]-catalyzed decomposition of {[(4-nitrophenyl)sulfonyl]imino}phenyl-13-iodane (NsN=IPh) resulted in formal insertions into CH bonds, activated by phenyl or vinyl groups, or by 0-substituents. Scope and limitations of the reaction were investigated. Yields of up to 84% were achieved in the most favorable cases. Yields were enhanced by electron-releasing substituents and decreased by steric hindrance. Aziridination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(88 citation statements)
references
References 67 publications
5
82
0
1
Order By: Relevance
“…Intermolecular amination experiments described by Müller using O 2 NC 6 H 4 SO 2 N=IPh (NsN=IPh) as the nitrene source underscore the value of certain rhodium(II) catalysts for C-H insertion (Scheme 17.5) [12,[34][35][36]. In accord with Breslow's finding, dirhodium carboxylates were demonstrated to catalyze the amination of allylic, benzylic, and adamantyl substrates.…”
Section: Intermolecular C-h Amination With Rhodium(ii) Catalystssupporting
confidence: 49%
“…Intermolecular amination experiments described by Müller using O 2 NC 6 H 4 SO 2 N=IPh (NsN=IPh) as the nitrene source underscore the value of certain rhodium(II) catalysts for C-H insertion (Scheme 17.5) [12,[34][35][36]. In accord with Breslow's finding, dirhodium carboxylates were demonstrated to catalyze the amination of allylic, benzylic, and adamantyl substrates.…”
Section: Intermolecular C-h Amination With Rhodium(ii) Catalystssupporting
confidence: 49%
“…In the rhodium case, some authors have proposed the concerted pathway, although not all the experimental evidences are in complete accord with this. For instance, work by Müller [103,126] proposed the one step mechanism on the basis of several experiments (also supported by Du Bois' studies) [127,128] whereas Dauban has shown some doubts due to the collection of contradictory data: [129] Hammett analyses supported the concerted pathway but KIE studies did not. DFT studies have shown that singlet and triplet states for Rh 2 -II, II -NR are very close in energy [130], and therefore small changes in the catalytic system could influence the reaction pathway.…”
Section: Mechanistic Considerationsmentioning
confidence: 94%
“…The results shown in Table 6.5 regarding the use of adamantane are somewhat those expected, since the reaction site, a tertiary C-H bond, is more prone to undergo the insertion that the secondary C-H bonds of cyclohexane. Muller's work provided 76 % of the amine derivatives, as a mixture (71:5) of the products formed from the functionalization of tertiary and secondary sites, respectively (Table 6.5, entry 2) [103]. Catalytic systems described by Che (Ru, Mn) [112,113], and Nicholas [114] (Zn) were similar in activity, but at lower temperatures (Table 6.5, entries 3-6).…”
Section: Cycloalkanes As Substratesmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, when MW heating was used, very poor results were obtained (Table 3, entry 41), again the silver-catalyzed reactions failed (Table 3, entries 40 and 42). For other terminal acyclic alkenes, such as oct-1-ene (1k), the HA took place in high yield only under solvent-free conditions using the gold complex as catalyst (Table 3, entries [43][44][45][46]. In this case, product 3ka was obtained together with regioisomeric sulfonamides at the 3-and 4-positions of the aliphatic skeleton, in 2/1.5/1 ratio.…”
Section: Au-vs Ag-catalyzed Hydroamination Of Alkenesmentioning
confidence: 99%